Titanium abutment background masking using highly opaque cements for implant prosthetics - Moecke, Sabrina Elise; Honorato Diniz, Ana Laura; Borges, Alessandra Boiler [UNESP]; Gomes Torres, Carlos Rocha [UNESP] (Mosher & Linder, Inc, 2023)
Purpose: To evaluate the capacity of highly opaque cements on masking titanium abutment background. Methods: Dentin and titanium specimens were used to simulate respectively, a natural dental background and an implant abutment. To simulate the full-crowns, Y-TZP zirconia (ZC), lithium disilicate (LD), and resin composite (RC) blocks were used. The titanium specimens were divided into six cementation groups (n=10): two regular cements (BQM and RX); three opaque cements (MHA; VA and BHA); and a clear liquid (CL). The masking capacity of each cement was calculated as the color difference between the color of the crowns over dentin with clear liquid (reference) and the color of the crowns over the titanium with the different cements (Delta Eab). Data were statistically analyzed using two-way ANOVA and Tukey test (alpha=0.05). Results: Significant differences (P= 0.0001) were observed for both factors, cement and crown, and for the interactions between them. The results of Tukey test for cement were: BHA-2.25(0.98), MHA-2.94 (1.03), VA-3.45 (1.67), BQM-9.55 (2.77), RX-9.88 (3.12), CL-10.41 (3.47). The cements BHA, MHA and VA showed significantly smaller means than BQM, RX and CL. The results for crown were: ZC-3.66 (2.37), LD-7.50 (4.08), RC-8.08 (4.67). The means for all crown materials were significantly different. Highly opaque cements were more efficient on background masking than regular cements. Zirconia promoted the higher color masking while the resin composite the lowest.